2022
DOI: 10.1007/s00405-022-07493-6
|View full text |Cite
|
Sign up to set email alerts
|

Texture analysis of conventional magnetic resonance imaging and diffusion-weighted imaging for distinguishing sinonasal non-Hodgkin’s lymphoma from squamous cell carcinoma

Abstract: Background: To evaluate the value of texture analysis (TA) of conventional magnetic resonance imaging (MRI) and diffusion-weighted imaging (DWI) in the differential diagnosis between sinonasal non-Hodgkin's lymphoma (NHL) and squamous cell carcinoma (SCC).Methods: Twenty-one patients with sinonasal SCC and 15 patients with NHL were retrospectively enrolled. TAs were performed on T2-weighted image (T2WI), apparent diffusion coe cient (ADC) and contrast-enhanced T1-weighted image (T1WI). Texture parameters, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…We also identified six articles from websites, citation searching, and suggestion. After applying the selection criteria, we identified eight articles with 440 patients (441 lesions) for systematic review and meta-analysis (9)(10)(11)(12)(13)(14)(15)(16). The extracted data from the eight studies are outlined in Supplementary Tables 1−3.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also identified six articles from websites, citation searching, and suggestion. After applying the selection criteria, we identified eight articles with 440 patients (441 lesions) for systematic review and meta-analysis (9)(10)(11)(12)(13)(14)(15)(16). The extracted data from the eight studies are outlined in Supplementary Tables 1−3.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…Head and neck malignant tumors have been shown to have lower ADC values than benign lesions (7,8). Although both head and neck cancers and lymphomas are highly cellular tumors, previous studies have shown that lymphomas tend to have particularly low ADC values (9)(10)(11)(12)(13)(14)(15)(16). However, due to the small sample sizes in most of the published series to date, the utility of ADC to distinguish extra-nodal lymphoma from head and neck cancers has not been definitively established.…”
Section: Introductionmentioning
confidence: 99%